Incidental Abdominal Aortic Aneurysm in the Psoriasis Patient: A Case Report and Review of Literature: - Akhoundi, Neda; Faghihi Langroudi, Taraneh; Shafizadeh, Kiarash; Jabbarzadeh, Mohamad Javad; Talebi, Sepehr (Galen Medical Journal, 2018)
Background: Psoriasis is defined as a chronic inflammatory disease involving keratinocytes hyperproliferation of the epidermis with the acceleration in the epidermal turnover time, which is affected by various factors including genetic, immunologic, and environmental factors. There is a high risk for the development of premature cardiovascular diseases among patients with psoriasis as well as one of the life-threatening events is an aortic aneurysm (AA). Case Report: We report a 60-year-old man with the diagnosed psoriatic disease that an enlargement of theÂ abdominal AA was incidentally found by annual check-up. Conclusion: Further large-scale studies are needed to find the prevalence of abdominal AA in psoriasis and the appropriate screening time of that in this disease.Â [GMJ.2018;7:e1168]